One size does not fit all: Cognitive enhancement as a multidimensional construct - Vranić, Andrea (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
Cognitive abilities are the key to success in almost all areas of life. Faster information processing and more efficient recall, greater (working) memory capacity and stronger inhibition of irrelevant stimuli, higher mental flexibility, and efficient associative memory, are some of the more specific cognitive processes underlying not just academic and professional success, but also success in everyday activities. Dynamic everyday life with an increasing flow of information places stronger and greater demands on our limited cognitive capacities. Recently, a larger number of strategies and interventions have been proposed, which are aimed at augmentation of brain functions and enhancement of processing capacities. Cognitive enhancement is relevant for a wide range of “users” - from children with ADHD or those raised in poverty, professionals with cognitively demanding workload, older adults with normative cognitive aging, to people with traumatic brain injuries or neurodegenerative diseases. Not surprisingly, the brain-training industry is one of the fastest growing market branches. Nevertheless, the (in)effectiveness of interventions has been the subject of long-standing controversy and argumentation among researchers. A synthesis of research from different scientific fields suggests that the answer to the effectiveness question requires a departure from the monolithic understanding of cognitive enhancement as a one-dimensional construct. If we accept its multidimensionality, we can discuss the effectiveness of interventions depending on their biochemical, physical, or behavioral nature, the targeted cognitive domain or process, the characteristics and individual variables of the participants, the duration of the intervention, and even the wider social acceptance of the idea of possible enhancement.